Penggunaan Model Pembelajaran Problem Based Learning (PBL) Untuk Meningkatkan Minat Belajar Peserta Didik Pada Materi “Kemampuanku Terbatas” Berbantu Media Audio Visual Fase D Kelas VII Dalam Pembelajaran Agama Katolik di SMP Regina Pacis Belitung - Monike Irene; Brigida Intan Printina (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This study aims to improve students' learning interest through the implementation of the Problem Based Learning (PBL) model, supported by audio-visual media, on the topic “Kemampuanku Terbatas” in Catholic Religious Education. This Classroom Action Research (CAR) was conducted at SMP Regina Pacis Belitung, Grade VII, involving 12 students. The focus of the research was to enhance students' engagement and learning motivation, which previously showed low levels of interest. The study was carried out in two cycles, each consisting of planning, action implementation, observation, and reflection. In the first cycle, the average score of students' learning interest reached 17.83, indicating sufficient participation but not yet optimal. Through the PBL intervention, using audio-visual media as a learning aid, the lessons became more interactive and engaging. In the second cycle, the average learning interest score increased to 20, with an average improvement of 2.17 points. These results demonstrate that the implementation of PBL, supported by audio-visual media, effectively enhances students' interest and engagement. The students became more active in solving problems and more motivated to participate in discussions and group learning activities. The visual media also contributed to a better understanding of the material. Based on these findings, it is recommended that the PBL model, complemented by audio-visual media, be applied in religious education to deepen understanding and increase students' learning interest.